2015
DOI: 10.1007/s00420-015-1079-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and insulin resistance in policemen working shifts

Abstract: It may be concluded that 12/24 shift system might give rise to insulin resistance and oxidative stress. Additionally, workers in this system may under risk of systemic inflammatory response. Working hours must be arranged in accordance with the physiological rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
1
9
0
1
Order By: Relevance
“…It has been reported that a number of key metabolic functions follow the circadian rhythms, 13 and epidemiological studies confirm that long‐term circadian misalignment associates with the development of insulin resistance, metabolic syndrome, and T2DM 14 . Animal experiments have confirmed that circadian rhythms of the T2DM classical model in db/db mice are disrupted completely 15 .…”
Section: Introductionmentioning
confidence: 93%
“…It has been reported that a number of key metabolic functions follow the circadian rhythms, 13 and epidemiological studies confirm that long‐term circadian misalignment associates with the development of insulin resistance, metabolic syndrome, and T2DM 14 . Animal experiments have confirmed that circadian rhythms of the T2DM classical model in db/db mice are disrupted completely 15 .…”
Section: Introductionmentioning
confidence: 93%
“…Epidemiological studies suggest that long-term circadian misalignment, such as occurs with shift work, is a risk factor for insulin resistance (13), type 2 diabetes (9), metabolic syndrome (27), obesity (10,16,52,55), hyperlipidemia (7), and nonalcoholic fatty liver disease (NAFLD) (34,35). There are various animal models to mimic human shift work, including altering the timing of food intake, activity, sleep, or light exposure (40).…”
Section: Introductionmentioning
confidence: 99%
“…So increased CRP due to reduced sleep could lead to systemic inflammation, but CRP is a nonspecific inflammatory marker and there are factors that might have role in association between night work and low grade inflammation including circadian disruption, poor sleep quality and reduce sleep duration. Nevertheless CRP can be a useful biomarker to assess the risk of future diabetes and metabolic syndrome, 39 it could be used to monitor metabolic risk in night shift workers. Metabolic risk and oxidative stress are grouped into high and low risk.…”
Section: Inflammatory Marker and Night Shiftmentioning
confidence: 99%